TI_GERICHTE 35.2023.88 vom 11. April 2024 , Trauma contusivo alla spalla destra. Ricaduta ex art. 11 OAINF. Sintomatologia a ponte. - TI Tribunale d'appello (2024)
Trauma contusivo alla spalla destra. Ricaduta ex art. 11 OAINF. Sintomatologia a ponte.